1998
DOI: 10.1177/002199839803202002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time and Temperature on the Flexural Strength of a Silica Particle Filled Epoxy Resin

Abstract: Composite materials that use an epoxy as a matrix resins have superior mechanical properties but these materials exhibit time and temperature behavior when used for long periods and under high temperatures. This time and temperature behavior has not been fully explained. The purpose of this paper is to further describe this time and temperature behavior, therefore increasing the reliability of these types of composite materials. The time and temperature dependence of flexural strength was examined by flexural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…McMurray and Amagi [3] studied the effect of temperature and stress ratio on fatigue strength of a silica-filled epoxy resin. They studied only one volume fraction (60%) of silica with an average size of 7 µm.…”
Section: Introductionmentioning
confidence: 99%
“…McMurray and Amagi [3] studied the effect of temperature and stress ratio on fatigue strength of a silica-filled epoxy resin. They studied only one volume fraction (60%) of silica with an average size of 7 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility to cyclic loading is particularly problematic because a crack will grow, however slowly, above a threshold range of stress intensities ΔK th that is significantly lower than the critical stress intensity K IC . Prevention of fatigue failure currently depends on accurate life prediction and implementation of inspection procedures.Polymer fatigue has been studied extensively in both homogeneous and composite structures (e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]). In most polymers, fatigue crack growth rates (da/dN) are accurately described by the Paris power law [16],…”
mentioning
confidence: 99%
“…reduce n, and (d) increasing the threshold ΔK th at which crack growth arrests. In the case of brittle thermosetting polymers, incorporation of a rubbery second phase [8][9][10], solid particles [11][12][13] or microcapsules [14,15] significantly improves fatigue performance by increasing the fracture toughness (Fig. 1a) and decreasing the Paris power law exponent (Fig.…”
mentioning
confidence: 99%
“…There is a keen interest to clarify the relevance of the primary properties of SiO 2 particles on the rheological characteristics of the composite system [1][2][3][4]. The study found that, the mechanical property of epoxy resin can be improved by the addition of nanoparticles in the epoxy resin.…”
Section: Introductionmentioning
confidence: 99%